Universal Śaivism The Appeasement of All Gods and Powers in the Śāntyadhyāya of the Śivadharmaśāstra - Bisschop, Peter (Gonda Indological Studies, 2018)
In Universal Śaivism Peter Bisschop provides a critical edition and annotated translation of the sixth chapter of the Śivadharmaśāstra `Treatise on the Religion of Śiva', the so-called Śāntyadhyāya 'Chapter on Appeasement'. The Sanskrit text is preceded by an extensive introduction on its composition, transmission and edition. The Śivadharmaśāstra has arguably played a crucial role in the formation, development and institutionalisation of Śaivism. Through a detailed study of its extensive śānti mantra, Peter Bisschop shows how the text advocates a system in which all worldly and cosmic power is ultimately dependent upon Śiva. The mantra itself is a mine of information on the evolving pantheon of early Brahmanical Hinduism. Thanks to generous support of the J. Gonda Fund Foundation, the e-book version of this volume is available in Open Access.